2020
DOI: 10.3389/fnins.2020.618019
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration-Dependent Retinal Remodeling: Looking for the Molecular Trigger

Abstract: Vision impairment and blindness in humans are most frequently caused by the degeneration and loss of photoreceptor cells in the outer retina, as is the case for age-related macular degeneration, retinitis pigmentosa, retinal detachment and many other diseases. While inner retinal neurons survive degeneration, they undergo fundamental pathophysiological changes, collectively known as “remodeling.” Inner retinal remodeling downstream to photoreceptor death occurs across mammalian retinas from mice to humans, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
(72 reference statements)
2
15
0
Order By: Relevance
“…We observed that, from early to intermediate AMD, the central RPE–BM was thicker, expectedly reflecting increased drusen load. Additionally, the majority of clusters within all retinal layers were less thinned and more thickened, which interestingly may reinforce potential inner retinal remodeling in AMD as described above, 68 , 72 – 74 such as cellular hyperactivity and membrane hyperpermeability, 95 although none (except the RPE–BM) reached statistical significance. Nevertheless, the consistent direction of differences from normal early and intermediate AMD eyes reaffirms that topographical thickness differences are mostly established from early AMD and strengthen the likelihood that AMD is a causative factor of these differences rather than some unmeasured variable or random chance.…”
Section: Discussionsupporting
confidence: 59%
“…We observed that, from early to intermediate AMD, the central RPE–BM was thicker, expectedly reflecting increased drusen load. Additionally, the majority of clusters within all retinal layers were less thinned and more thickened, which interestingly may reinforce potential inner retinal remodeling in AMD as described above, 68 , 72 – 74 such as cellular hyperactivity and membrane hyperpermeability, 95 although none (except the RPE–BM) reached statistical significance. Nevertheless, the consistent direction of differences from normal early and intermediate AMD eyes reaffirms that topographical thickness differences are mostly established from early AMD and strengthen the likelihood that AMD is a causative factor of these differences rather than some unmeasured variable or random chance.…”
Section: Discussionsupporting
confidence: 59%
“…RGC hyperactivity results partly from changes in presynaptic neurons ( 18 , 19 ) and partly from changes intrinsic to RGCs, including up-regulation of voltage-gated ion channels, which increases membrane excitability ( 11 ), and up-regulation of ligand-gated channels, which increases resting membrane permeability ( 20 ). Recent studies indicate that retinoic acid (RA) is the signal that triggers morphological ( 21 ) and physiological ( 17 , 22 ) remodeling. Adding exogenous RA to healthy retinas mimics remodeling, adding RA receptor (RAR) inhibitors to degenerated retinas suppresses remodeling, and increased RA-induced gene expression can be detected in degenerated retinas ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The light responses and spontaneous neuron firing were dramatically hyperexcited in the Rho P23H/WT mouse V1 (Figures 3 and 5). The observed hyperexcitability is well in line with previous literature, demonstrating increased neural noise originating from the inner retina (Borowska et al ., 2011; Menzler and Zeck, 2011; Trenholm and Awatramani, 2015; Haselier et al ., 2017; Telias et al ., 2020). Further, as similarly indicated by the OMR behavior (Figure 2), Rho P23H/WT mouse V1 neurons preferred lower SFs compared to WT mice (Figure 6E), indicating increasing retinal ganglion cell (RGC) receptive fields.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to clinical correlates, corresponding anatomical data have been obtained from patient retinas post mortem (Jones et al ., 2016). Such studies have demonstrated robust rewiring of neural connections, commonly referred to as ” remodeling”, leading to dramatically increased spontaneous neural activity, decreased signal-to-noise ratios, and attenuated light responses in the inner retina (Toychiev et al ., 2013; Trenholm and Awatramani, 2015; Haselier et al, 2017; Telias et al ., 2020). Much concern has been raised that retinal remodeling may preclude restoration of visual function even if augmentation of photoreception by various advanced therapies could be achieved (Marc et al ., 2014; Reh, 2016; Foik et al ., 2018; Suh et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%